Experimental and ab initio study of the structural and optical properties of ZnO coatings: performance of the DFT+U approach - Apaolaza, Agustín (2020)
In this work, ZnO coatings were produced by the spray-pyrolysis technique and characterized by scanning electron microscopy, X-ray diffraction and optical transmittance spectroscopy. The experimental results were compared to predictions obtained from electronic-structure calculations based on the Density Functional Theory plus U (DFT+U) approach. To this purpose, the 2H, 4H and 6H polytypes of ZnO were theoretically analysed, and DFT+U was assessed for the calculation of structural, electronic and optical properties of the hexagonal ZnO structures. We found that DFT+U is an effective and accurate method that combined with experimental measurements, allows a deeper insight about the coatings of the wurtzite (2H) phase synthesized in the laboratory. This comprehensive study of the pure ZnO is the first step towards the study of more complex ZnO-based coatings.